Determination of BRAF V600E (VE1) protein expression and BRAF gene mutation status in codon 600 in borderline and low-grade ovarian cancers - Pawel Sadlecki; Pawel Walentowicz; Magdalena Bodnar; Andrzej Marszalek; Marek Grabiec; Malgorzata Walentowicz-Sadlecka (Tumor Biology, 2017)
Epithelial ovarian tumors are a group of morphologically and genetically heterogeneous neoplasms. Based on differences in clinical phenotype and genetic background, ovarian neoplasms are classified as low-grade and high-grade tumor. Borderline ovarian tumors represent approximately 10%–20% of all epithelial ovarian masses. Various histological subtypes of ovarian malignancies differ in terms of their risk factor profiles, precursor lesions, clinical course, patterns of spread, molecular genetics, response to conventional chemotherapy, and prognosis. The most frequent genetic aberrations found in low-grade serous ovarian carcinomas and serous borderline tumors, as well as in mucinous cancers, are mutations in BRAF and KRAS genes. The most commonly observed BRAF mutation is substitution of glutamic acid for valine in codon 600 (V600E) in exon 15. The primary aim of this study was to determine whether fully integrated, real-time polymerase chain reaction–based Idylla™ system may be useful in determination of BRAF gene mutation status in codon 600 in patients with borderline ovarian tumors and low-grade ovarian carcinomas. The study included tissue specimens from 42 patients with histopathologically verified ovarian masses, who were operated on at the Department of Obstetrics and Gynecology, Nicolaus Copernicus University Collegium Medicum in Bydgoszcz (Poland). Based on histopathological examination of surgical specimens, 35 lesions were classified as low-grade ovarian carcinomas, and 7 as borderline ovarian tumors. Specimens with expression of BRAF V600E (VE1) protein were tested for mutations in codon 600 of the BRAF gene, using an automated molecular diagnostics platform Idylla™. Cytoplasmic immunoexpression of BRAF V600E (VE1) protein was found in three specimens: serous superficial papilloma, serous papillary cystadenoma of borderline malignancy, and partially proliferative serous cystadenoma. All specimens with the expression of BRAF V600E (VE1) protein were tested positively for BRAF V600E/E2/D mutation. No statistically significant relationship (p > 0.05) was found between the presence of BRAF V600E mutation and the probability of 5-year survival. BRAF mutation testing with a rapid, fully integrated molecular diagnostics system Idylla™ may be also a powerful prognostic tool in subjects with newly diagnosed serous borderline tumors, identifying a subset of patients who are unlikely to progress.